Induction of the proapoptotic tumor suppressor gene Cell Adhesion Molecule 1 by chemotherapeutic agents is repressed in therapy resistant acute myeloid leukemia. Issue 12 (9th December 2014) - Fisser, Muriel C.; Rommer, Anna; Steinleitner, Katarina; Heller, Gerwin; Herbst, Friederike; Wiese, Meike; Glimm, Hanno; Sill, Heinz; Wieser, Rotraud
<x xml:space="preserve">Abstract</x> Even though a large proportion of patients with acute myeloid leukemia (AML) achieve a complete remission upon initial therapy, the majority of them eventually relapse with resistant disease. Overexpression of the gene coding for the transcription factor Ecotropic Virus Integration site 1 (EVI1) is associated with rapid disease recurrence and shortened survival. We therefore sought to identify EVI1 target genes that may play a role in chemotherapy resistance using a previously established in vitro model system for EVI1 positive myeloid malignancies. Gene expression microarray analyses uncovered the Cell Adhesion Molecule 1 (CADM1) gene as a candidate whose deregulation by EVI1 may contribute to drug refractoriness. CADM1 is an apoptosis inducing tumor suppressor gene that is inactivated by methylation in a variety of tumor types. In the present study we provide evidence that it may play a role in chemotherapy induced cell death in AML: CADM1 was induced by drugs used in the treatment of AML in a human myeloid cell line and in primary diagnostic AML samples, and its experimental expression in a cell line model increased the proportion of apoptotic cells. CADM1 up‐regulation was abolished by ectopic expression of EVI1, and EVI1 expression correlated with increased CADM1 promoter methylation both in a cell line model and in primary AML cells. Finally, CADM1 induction was repressed in primary samples from AML patients at relapse. In summary, these data suggest that failure to up‐regulate CADM1 in response to chemotherapeutic drugs may contribute to therapy resistance in AML. © 2014 The Authors. Molecular Carcinogenesis published by Wiley Periodicals, Inc.